Strategic orientations, generic strategies, and export performance: a meta-analysis - Scholz, Laura (2018)
Purpose – The current state of research about determinants of export performance is characterized by fragmentation and conceptual confusion leading to a substantial lack of generalizability. The underlying study analyzes strategic orientations as internal determinants of export performance, being mediated by the generic strategy of differentiation. The author’s goal is to (1) synthesize existing empirical studies and meta-analytically cumulate the correlations, (2) test whether a firm’s generic strategy is a mediator of the relationship between strategic orientations and export performance, and (3) proof empirically that the strategic orientations do not operate in isolation, but rather have joint effects. Theory development – First, the relationship between the strategic orientations and export performance is proposed. Second, the strategic orientations are brought into relation with the generic strategy of differentiation. Third, a positive correlation between differentiation strategy and export performance is suggested. Finally, hypotheses are formulated that propose a direct mediation effect of differentiation in the relation of the strategic orientations and export performance. An explorative question is developed pointing out a possible common effect of the orientations on export performance that shall be tested using Commonality Analysis. Methodology – In order to study the nature of the aforementioned relationships as well as their contingencies the underlying study utilizes bivariate meta-analysis. The inquiry is based upon 126 studies comprising 307,877 independent samples (N=307,877). Structural Equation Modeling serves as a tool to test the proposed mediation model for its goodness-of-fit. In order to test for unique and common effects, a Commonality Analysis is conducted. Results – Strategic orientations correlate positively and statistically significantly with export performance as well as differentiation, supporting Hypotheses 1 and 2. The variables with the highest correlation coefficient are technology orientation and entrepreneurial orientation. In support of Hypothesis 3, the differentiation strategy is positively and statistically significantly related to export performance. In the Structural Equation Model, the partial mediation model turns out to have the highest fit, suggesting a partial mediation of differentiation between the strategic orientations and export performance (Hypothesis 4). The Commonality Analysis reveals that the common effects among the strategic orientations and differentiation have higher explanatory power than the unique effects. This result hints at the importance of a simultaneous pursuit of the strategic orientations in practice. Discussion – Practical implications of the findings point out the necessity to shift the view on strategic orientations and hence not looking at them as alternative, but rather as complementary approaches. For theory, this implies that the focus of research must shift towards the joint consideration of the variables. Additionally, the operationalization of technology orientation must be revised since it has a fuzzy content domain, even though it is found to be one of the most influencing variables in the proposed model.